Hoʻopili: Exploring social sciences from the ʻāina - Aquino, Kamakanaokealoha M. (New Zealand Sociology, 2026)
Decolonising and indigenising the academy continues to be a trend for higher educational institutions around the world. As a result of the 2012 Ke Au Hou Native Hawaiian Advancement Task Force Report, Hui ʻĀina Pilipili, the Native Hawaiian Initiative, was established to provide a coordinated effort to decolonise and indigenise the College of Social Sciences at the University of Hawaiʻi at Mānoa. This article explores what is means to re(create) social sciences from a Hawaiian perspective. It concludes with reflections on the ways in which the College of Social Sciences has made progress in its commitment to a Hawaiian place of learning.